Desire - Fabo, Andy (Ottawa : Artists' Centre d'artistes (Galerie 101), 1984)
Johnson, Rae ; Gregson, Sandra ; Harwood, Simon ; Fernie, Lynn ; Waugh, Phyllis ; Merrill, Michael ; Wilson, Tony ; Coad, Wendy ; Andrews, Stephen ; Girling, Oliver ; Jocelyn, Tim ; Goldstein, Sybil ; Flack, Rob ; Tod, Joanne ; Besselink, Fred ; Gilles, Suzanne
Desire, Galerie 101, Ottawa, February 14 - March 10, 1984
boek